Public Finance - Rosen, Harvey S.;Gayer, Ted (Boston, 2008)
Includes material and examples from public finance literature and policy world. This book contains substantive changes that reflect progress that has been made in the field of public finance. It draws on links between economic analysis and political issues.
Includes Index.
Keywords: Finance, Public; Finance, Public United States; USA